Perancangan Desain High Fidelity User Interface pada Prototype Game Role-Playing Game 2D Top-Down - Ainan Fajar Fatcha; Agus Aan Jiwa Permana; Ketut Agus Seputra (Lembaga Yasin AlSys, 2026)
The rapid growth of the global game industry has increased competition among developers, making the quality of user interface (UI) design an important factor in shaping an optimal gaming experience. Although indie game development continues to grow, studies that specifically address high-fidelity UI design for 2D top-down role-playing game (RPG) prototypes remain limited. This study aimed to design and evaluate a high-fidelity UI prototype for a 2D top-down RPG game titled Dungeon Realm. This study employed a design and development approach guided by the Game Development Life Cycle (GDLC) methodology, which includes the initiation, preproduction, production, and testing phases. The design process began with capturing environment screenshots from Godot Engine as contextual background references, followed by the development of a high-fidelity prototype using Figma. The resulting prototype consisted of six UI screens, namely Main Menu, In-Game HUD, Pause Menu, Game Over, Settings, and How to Play. The evaluation was conducted through black box testing to verify the functional navigation flow across all interface screens, involving the researcher and two additional testers. The results showed that all defined navigation scenarios functioned according to the predetermined expected outputs, thereby confirming the structural integrity of the prototype design. These findings contribute to the application of user-centered design principles in game UI development and expand understanding of high-fidelity prototyping in indie RPG projects. This study concludes that systematic UI prototype design using the GDLC methodology can produce a coherent, navigable game interface with a validated design foundation before full implementation in Godot Engine.